Management of Uncertainty Theory and Application in the Design of Systems and Organizations - Grote, Gudela (Decision Engineering,, 2009)
The handling of uncertainties stemming from internal processes and the environment is a core issue in organizational and system design. Management of Uncertainty examines the necessity of living with technical and organizational uncertainties, or even taking advantage of them without losing the stability created by reducing uncertainty. With overall uncertainty increasing as a result of faster innovation cycles, more dynamic environments, and growing interconnections in organizational networks, socio-technical systems have to continuously adjust the balance between stability and flexibility in order to secure successful performance. Building on concepts from organization theory, control theory, decision theory, and work and organizational psychology, a decision process is proposed that supports systematic evaluation of the costs and benefits of reducing, maintaining, or increasing uncertainty in a particular context. Also, the individual and collective belief systems that influence cost-benefit perceptions are considered. Consequences for the design of automation, planning systems, organizational rulebooks, safety management systems and also human resource management are drawn. Management of Uncertainty will be a useful tool for postgraduate researchers, as well as for operational and strategic decision-makers in organizations. It offers a number of concrete instruments for organizational and system design, which are further illustrated by a range of case studies. The Decision Engineering series focuses on the foundations and applications of tools and techniques related to decision engineering, and identifies their relevance in 'engineering' decisions. The series provides an aid to practising professionals and applied researchers in the development of tools for informed operational and business decision making, within industry, by utilising distributed organisational knowledge.